A Model For Froth-Phase Recovery - H. Do (Society for Mining, Metallurgy & Exploration, 2008)
In flotation, hydrophobic particles are selectively collected by air bubbles, and the bubble-particle aggregates enter the froth phase. However, less hydrophobic particles drop off from the froth phase, while more hydrophobic particles are recovered. Thus, the froth phase provides an important cleaning mechanism. In the present communication, the froth-phase recovery process has been modeled by considering particle retention times and the carrying capacities of bubbles. The model predictions are compared with the experimental data reported by Seaman et al. (2006). The results show that the froth-phase recovery varies with particle size, particle hydrophobicity, and bubble coarsening.